Postthyroidectomy Horner's Syndrome. (21st October 2012) - Vilallonga, Ramon; Fort, José Manuel; Mazarro, Alejandro; Gonzalez, Oscar; Caubet, Enric; Romero, Giancarlo; Armengol, Manel
Abstract : Horner's syndrome (HSd) results from an injury along the cervical sympathetic chain, producing ipsilateral miosis, ptosis, enophthalmos, and facial anhydrosis. Although more commonly associated to malignant tumors affecting the preganglionar segment of the sympathetic chain (especially in the lung apex), HSd has been described as a rare complication of thyroid surgery. We herein report a case of HSd after completing total thyroidectomy.